The Effectiveness of Emotion-Focused Therapy on Attachment Disorders in Cancer Patients at Milad Hospital, Isfahan - Asadi Kashani, Marzieh; Samani, Siamak; Sohrabi Shegefti, Nadereh (KMAN Counseling & Psychology Nexus, 2025)
The aim of this study is to investigate the effectiveness of emotion-focused therapy (EFT) on attachment disorders in cancer patients at Milad Hospital, Isfahan. Attachment, as an internal working model, is considered a key factor in regulating individuals' psychological security, and its disorders can lead to serious psychological and physical problems in cancer patients. This study employed a quasi-experimental pre-test and post-test design with a control group. The research sample consisted of 40 cancer patients with insecure attachment styles, who were randomly assigned to experimental (EFT) and control (no intervention) groups. Emotion-focused therapy was conducted in 10 group sessions, each lasting 45 minutes. The measurement tool used was the Hazan and Shaver Attachment Styles Questionnaire. The results of covariance analysis indicated that emotion-focused therapy significantly reduced avoidant and ambivalent attachment and increased secure attachment in the experimental group compared to the control group. The findings suggest that emotion-focused therapy can have a significant impact on improving the attachment status of cancer patients. These results are consistent with previous studies and highlight the importance of considering non-pharmacological psychological therapies to enhance the quality of life in cancer patients. Finally, it is recommended that emotion-focused therapy be incorporated into cancer treatment programs to reduce psychological issues and improve the patients' mental and social well-being.